Neural Correlates of Duration Discrimination in Young Adults with Autism Spectrum Disorder, Attention-Deficit/Hyperactivity Disorder and Their Comorbid Presentation - Lukito, Steve D.; O'Daly, Owen G.; Lythgoe, David J.; Whitwell, Susannah; Debnam, Amanda; Murphy, Clodagh M.; Ashwood, Karen; Stoencheva, Vladimira; Simonoff, Emily; Rubia, Katya (Frontiers in Psychiatry, 2018)
Attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) often co-occur and share neurocognitive deficits. One such shared impairment is in duration discrimination. However, no studies using functional magnetic resonance imaging (fMRI) have investigated whether these duration discrimination deficits are underpinned by the same or different underlying neurofunctional processes. In this study, we used fMRI to compare the neurofunctional correlates of duration discrimination between young adult males with ASD (n = 23), ADHD (n = 25), the comorbid condition of ASD+ADHD (n = 24) and typical development (TD, n = 26) using both region of interest (ROI) and whole brain analyses. Both the ROI and the whole-brain analyses showed that the comorbid ASD+ADHD group compared to controls, and for the ROI analysis relative to the other patient groups, had significant under-activation in right inferior frontal cortex (IFG) a key region for duration discrimination that is typically under-activated in boys with ADHD. The findings show that in adulthood, only the comorbid ADHD + ASD, but not the pure conditions, shows neurofunctional deficits in a typical duration discrimination region.